PENGARUH KESIAPAN MODAL DAN LITERASI KEUANGAN TERHADAP KINERJA UMKM - Surahmi Sahruddin; Halim Usman; Nispa Sari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the effect of capital readiness and financial literacy on the performance of MSMEs (micro, small and medium enterprises) in Luwu district. This research is a quantitative descriptive study using a sample of 100 MSMEs in Luwu district. The sampling technique in this research is random sampling. The data collection method is through surveys and the data analysis technique uses multiple linear regression tests. The research results show that capital readiness and financial literacy have a positive influence on the performance of MSMEs. This research proves the importance of financial literacy in improving the performance of MSMEs, with capital readiness as a supporting factor.